DECONSTRUCTING THE CHARACTERS IN SOPHOCLES’ OEDIPUS REX - Meluk, Oktavianus T; Wanggai, Febe F I; Liru, Marianus W (Lantern: Journal of Language and Literature, 2023)
This study aimed at finding the characteristics of the characters in Sophocles' Drama Oedipus Rex, as well as to deconstruct the characterization of the characters that have been found and brought out the other side of the characteristics of each character. Descriptive qualitative method was used to analyze the data in this study. The data were analyzed by reading and selecting data from the utterances in the drama dialogue. Then the data were analyzed using deconstruction theory on the characterization of the characters in the drama. The theory used was the deconstruction theory discovered by Jacques Derrida. The result of the analysis shows that firstly, the characters are Oedipus, Jocasta, Creon, and Tiresias. Each character has characteristics. Oedipus has the characteristics of being wise, brave, and is also a helpful figure. Jocasta is a kind character, Creon is a fair figure, and Tiresias is a wise figure. However, after being deconstructed, each characteristic has opposite characteristics so that the other side can be revealed. Oedipus is characterized as a silly, a coward, and a betrayer figure. Jocasta has bad characteristics. Meanwhile, Creon has unfair characteristics, and Tiresias has a selfish characteristic.